PENINGKATAN KUALITAS HIDUP LANSIA MELALUI PELAYANAN KESEHATAN DAN EDUKASI KESEHATAN SECARA PERSONAL PADA LANSIA DI BANJAR PAYANGAN DESA, PAYANGAN, GIANYAR - Ni Luh Putu Eka Diarthini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
ABSTRACT Elderly is someone whose age reaches 60 years and over. With increasing age, the aging process occurs which can cause health problems. This activity was carried out in Banjar Payangan Village, Melinggih Village, Payangan District, Gianyar Regency, with the target of all the elderly there. The purpose of this service is to provide health services to the elderly in Banjar Payangan Desa, to create healthy, quality, and productive elderly people in their old age. The method of service that is carried out does not only provide services in curative efforts, but also focuses on promotive and preventive efforts carried out by providing personal health counseling. Activities carried out by checking the health of the elderly by a team of doctors from the Department of Parasitology, Faculty of Medicine, UNUD, such as checking blood pressure, pulse, body temperature and blood sugar levels as well as providing treatment for the sick and providing vitamins to maintain the health of the elderly. The results of this activity were 106 elderly people who were registered as Werda Kusuma in Banjar Payangan Desa. All elderly received a health examination with the result that the dominant diseases suffered by the elderly in the banjar were hypertension (37/106) 34.91% and arthritis (31/106) 29.24%. With the implementation of these various health services, it is hoped that it can improve the quality of life of the elderly in Banjar Payangan Desa. Keywords: health services, the elderly, quality of life, education